Secular trend of Kawasaki disease and its correlation with viral activity in Taiwan: a nationwide population-based study - Wei-Liang Shih; Li-Min Huang; Mei-Hwan Wu; Luan-Yin Chang (BMC, 2024)
Abstract Background Kawasaki disease (KD) is the most important acquired heart disease in children. This study investigated annual incidence, seasonality, secular trend and the correlation of KD incidence with viral activity in Taiwan. Methods Through the national health insurance database, we identified KD during 2001-2020. The viral activity was obtained from nationwide surveillance database. We analyzed KD age-specific annual incidence, secular trends, seasonality and the correlation between KD incidence and common enteric or respiratory viral activity. Results The KD incidence of subjects younger than 18 years significantly increased from 2001 to 2020 (11.78 and 22.40 per 100,000 person-years, respectively), and substantially decreased with age. Infants younger than 1 year presented the highest KD annual incidence at 105.82 to 164.34 per 100,000 person-years from 2001 to 2020. For all KD patients, the most frequently occurring season was summer followed by autumn. The KD incidence of infants younger than 1 year had significantly positive correlation with enteric (r = 0.14) and respiratory (r = 0.18) viral activity. Conclusions This study demonstrates the increasing trend of KD annual incidence and seasonality (more in summer and autumn) in Taiwan. The activity of common respiratory and enteric viruses was significantly correlated with KD incidence in infants.